Comment on “Educational philosophy and educational practice in Confucianism” - Zhang, Ling (2024)
Commented article: XU, Yushu; CHEN, Chao. Educational philosophy and educational practice in Confucianism. Trans/Form/Ação: Unesp journal of philosophy, Marília, v. 47, n. 5, “Eastern thought 2”, e02400189, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14955.